Auditoría Financiera al Gobierno Autónomo Descentralizado Parroquial de Chantaco del Cantòn y Provincia de Loja, Periodo 2015 - Yaguana Morocho, Ruth Elizabeth (2017)
The work titled "FINANCIAL AUDIT TO THE AUTONOMOUS DECONRALIZED AUTONOMOUS GOVERNMENT OF CHANTACO DEL CANTÒN AND PROVINCE OF LOJA, PERIOD 2015," was developed with the purpose of Evaluating the Internal Control System implemented in the entity, considering the sector to which it belongs, for This was applied audit programs and control questionnaires for the subcomponents: current assets were found to have a confidence level of 89.19%, non-current assets confidence level 83.33%, liabilities confidence level 96.29% , Equity 100% confidence level, income confidence level 92.86%, expenditure confidence level 93.33% which is estimated a high level of reliability and a low risk; In addition to verifying compliance with the legal, regulatory and regulatory provisions applicable to the execution of the economic activities that govern the entity, in relation to the applied methodology was developed in its three phases of audit that are: PHASE I- A Planning Preliminary, the previous visit to the institution was made, to know the activities that it performs, the PHASE IB Specific Planning in which it refers to the determination of the materiality, risk assessment and the approach of the audit, PHASE II Of Execution, Where the audit and development programs of work papers were applied as questionnaires determining the following findings: no bank reconciliations are carried out, there is no inventory of fixed assets, no segregation of functions, inadequate file of supporting documents, which 5 Were developed in the respective Narrative Cédulas Narrativas, PHASE III Of the Report here profound in the findings that were found elaborating the respective Analytical Notes; As last we have to present a report containing the results obtained from the Financial Audit applied, with the respective comments, conclusions and recommendations of contributing to the better functioning of the entity, which the highest authority should execute in the shortest possible time, to guarantee the accuracy of the results obtained, helping the correct Decision-making processes that contribute to its development.